Research of storable and ready-to-use artificial red blood cells (hemoglobin vesicles) for emergency medicine and other clinical applications - Sakai, Hiromi; Kure, Tomoko; Taguchi, Kazuaki; Azuma, Hiroshi (Frontiers in Medical Technology, 2022)
Hemoglobin (Hb) is the most abundant protein in blood, with concentration of about 12–15 g/dl. The highly concentrated Hb solution (35 g/dl) is compartmentalized in red blood cells (RBCs). Once Hb is released from RBCs by hemolysis during blood circulation, it induces renal and cardiovascular toxicities. To date, hemoglobin-based oxygen carriers of various types have been developed as blood substitutes to mitigate the Hb toxicities. One method is Hb encapsulation in phospholipid vesicles (liposomes). Although the Hb toxicity can be shielded, it is equally important to ensure the biocompatibility of the liposomal membrane. We have developed Hb-vesicles (HbV). A new encapsulation method using a rotation-revolution mixer which enabled efficient production of HbV with a high yield has considerably facilitated R&D of HbV. Along with our academic consortium, we have studied the preclinical safety and efficacy of HbV extensively as a transfusion alternative, and finally conducted a phase I clinical trial. Moreover, carbonyl-HbV and met-HbV are developed respectively for an anti-inflammatory and anti-oxidative agent and an antidote for poisons. This review paper specifically presents past trials of liposome encapsulated Hb, biocompatible lipid bilayer membranes, and efficient HbV preparation methods, in addition to potential clinical applications of HbV based on results of our in vivo studies.